Sensibilidade do WISC-III na identificação do Transtorno de Déficit de Atenção/Hiperatividade(TDAH) - Regina Maria Fernandes Lopes; Marianne Farina; Guilherme Welter Wendt; Cristiane Silva Esteves; Irani I. de Lima Argimon (CAEN, 2012)
Attention deficit hyperactivity disorder (ADHD) is characterized by decreased attention span, impulsivity and hyperactivity, affecting children, adolescents and adults. There are several tools that can aid in the diagnosis of this disorder and one of them is the index of resistance to distractibility (IRD) of the WISC-III Digit Span and Arithmetic subtests. Objective: To evaluate, through the Wechsler Intelligence Scale III (WISC III), the intelligence quotient (IQ) Global, Verbal and Performance and measure the performance indices in Factorials and identifying whether or not the presence of ADHD. Method: Design quantitative transversal. Sample of 80 participants, aged 6-15 years, 26 females and 54 males. Results: Of the participants assessed, 67.5% had ADHD. The majority of this percentage had an IQ in the medium term, and those who did not have ADHD have a much higher IQ. Conclusion: The WISC-III is shown to be sensitive in the diagnosis of children with ADHD and is a useful tool to assist in the evaluation of children with this disorder